The key to Rondo - Rodda, Emily (New York : Scholastic Press, 2008)
Through an heirloom music box, Leo, a serious, responsible boy, and his badly-behaved cousin Mimi enter the magical world of Rondo to rescue Mimi's dog from a sorceress, who wishes to exchange him for the key that allows free travel between worlds.
School Library Journal
Wilson's Children
Wilson's Junior High School
4.9
3-6.
3-6
Keywords: Adventure and adventurers -- Juvenile fiction; Cousins -- Juvenile fiction; Magic -- Juvenile fiction; Music box -- Juvenile fiction; Space and time -- Juvenile fiction; Witches -- Juvenile fiction; Adventure and adventurers -- Fiction; Cousins -- Fiction; Magic -- Fiction; Music box -- Fiction; Space and time -- Fiction; Witches -- Fiction; Adventure fiction; Cousins -- Fiction; Magic -- Fiction; Music boxes -- Fiction; Space and time -- Fiction; Witches -- Fiction